Effect of dietary resveratrol supplementation on muscle fiber types and meat quality in beef cattle. (December 2022) - Li, Jiqiang; Liang, Rongrong; Mao, Yanwei; Yang, Xiaoyin; Luo, Xin; Qian, Zhanyu; Zhang, Yimin; Zhu, Lixian
Abstract: In order to investigate the effect of dietary resveratrol supplementation on muscle fiber types and meat quality in beef cattle, a feeding experiment was undertaken. Longissimus lumborum, Psoas major and Semitendinosus muscles were collected 24 h post-mortem from two groups of cattle, which were fed with a total mixed ration (Control – CON) or supplemented with resveratrol (5 g/animal/day, RES) for 120 d before slaughter. The results showed that dietary resveratrol increased the gene expression of MyHC I and enhanced the proportion of type I fibers in three muscles. The cooking loss and Warner-Bratzler shear force of all muscles during aging for 21 days were decreased. However, the increased proportion of type I fibers resulted in a darker initial color, but did improve color stability, as the a * value of RES samples was lower initially but higher in the later stage of aging. This study indicates the supplementation potential of resveratrol for beef cattle for tenderness and color stability.